David Beniuk interviewed by Rob Willis in the Rob and Olya Willis folklore collection. - Beniuk, David, 1969-; Willis, Rob, 1944-; Willis, Olya. (2018)
Folkloric recording.
Recorded with Olya Willis.
Recorded on 21 May 2018 in Hobart, Tasmania.
Timed summary available.
Keywords: Beniuk, David, -- 1969- -- Interviews; Culprits (Musical group); Merry Widows (Musical group); Journalists -- Tasmania -- Interviews; Musicians -- Tasmania -- Interviews; Folk music -- Australia